A novel architecture to monetize digital offerings. Issue 6 (14th December 2018) - Reisman, Richard; Bertini, Marco
Abstract As commerce continues to shift to the digital domain, organizations respond by improving and evolving their approach to creating value for customers. When the time comes to convert digital anything into cash they can bank, the same organizations, however, seem stuck in time. The purpose of the article is to highlight this inconsistency and, importantly, propose a solution. First, we leverage the literature on freemium and participative pricing mechanisms to lay the foundations for a revenue architecture fit for the digital economy. We argue in favor of three building blocks: empowerment, dialog, and reputation. Second, we describe FairPay as a promising configuration of these factors.